The Effect of Health Education through the Mobile-Based Application My Minds on Adolescents’ Knowledge in Preventing Mental Health Disorders and Behavior - May Muslim; Nurhalinah Nurhalinah; Meivi Sasanelvira (Indonesian Journal of Global Health Research, 2025)
This study aimed to determine the effect of health education through the mobile-based application My Minds on adolescents' knowledge in preventing mental health disorders in Kuningan Regency in 2025. The research method employed a quasi-experimental design with a pretest-posttest and control group. The population consisted of 10th-grade students from two senior high schools in Kuningan Regency, with a sample of 42 students in each intervention and control group.  The research design was a quasi-experimental one. Quasi-experimental research is an experiment that uses a specific design and/or a non-random method for allocating research factors, resulting in a controlled research situation that approximates the situation expected from an experiment, The research design used in this study was a pretest-posttest design with a control group.The instrument used was The Strengths and Difficulties Questionnaire (SDQ), and bivariate analysis was conducted using the Mann-Whitney test. Results showed a significant difference between the My Minds application group (mean score 75.19) and the lecture method group (mean score 72.38) with a p-value of 0.035. In conclusion, the My Minds application is more effective in increasing adolescents' knowledge in preventing mental health disorders.